A comunicação de más notícias ao longo da graduação em medicina: reflexões de uma jornada pessoal e profissional - Silva, Maria Vitoria Gomes da (Universidade Federal de São Carlos, 2024)
Effective communication is an essential skill in the practice of medical professionals, relating directly to the doctor-patient relationship that will be established and influencing personal perspectives and decision-making. In this context, communicating bad news is something that is part of everyday medical life and must be transmitted in the best possible way, both for the well-being of the patient and the medical professional. This course conclusion work seeks to narrate the experience of a medical student throughout the six years of graduation amidst the theme of communicating bad news, and to describe in a reflective way, how the nuances of this topic accompanied her throughout her career. time. It is possible to see that from the initial contact with the topic, in the first year of graduation, it was present in different professional and personal contexts and little by little it was integrated into the clinical practice of the professional in training.
Communicating bad news during medical graduation: reflections on a personal and professional journey
Keywords: Medicina; Comunicação más notícias; Formação médica; relato de experiência; Medicine; Medical education; Breaking bad news communication; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA